Changing trends in the disease burden of primary liver cancer caused by specific etiologies in China. (6th August 2019) - Liu, Zhenqiu; Mao, Xianhua; Jiang, Yanfeng; Cai, Ning; Jin, Li; Zhang, Tiejun; Chen, Xingdong
Abstract: Background: Liver cancer is a commonly diagnosed malignancy in China. The etiologies of liver cancer are widely known, although studies on temporal trends in liver cancer caused by specific etiologies are rare. Methods: Data on the incidence and mortality of liver cancer were retrieved from the Global Burden of Diseases Study 2017. The estimated annual percentage change (EAPC) was used to quantify temporal trends in the age‐standardized incidence rate (ASIR) and the age‐standardized mortality rate (ASMR) of liver cancer from 1990 to 2017. Results: Nationwide, the number of incident cases of liver cancer increased from 258 000 in 1990 to 515 900 in 2017. The ASIR decreased from 27.16 per 100 000 to 26.04 per 100 000 during this period, with an EAPC of −0.64 (95% confidence interval [CI] −0.84, −0.44). The number of deaths increased from 245 300 in 1990 to 418 200 in 2017, and the ASMR decreased from 26.72 to 21.30 (EAPC = −1.16, 95% CI −1.35, −0.97). The most pronounced decreases in the ASIR and ASMR were observed in liver cancer due to hepatitis B and in people aged 15‐49 years. Conclusions: Since the extensive efforts for prevention of hepatitis B virus infection, the incidence of liver cancer due to hepatitis B has significantly decreased. However, liver cancer due to hepatitis C, NASH, and other causes remains a major public health concern. Additional preventive strategies tailored to liver cancer are needed to further reduce its disease burden in China. Abstract : Since the extensive efforts for prevention of hepatitis B virus infection, the incidence of liver cancer due to hepatitis B has significantly decreased. However, liver cancer due to hepatitis C, NASH, and other causes remains a major public health concern. Additional preventive strategies tailored to liver cancer are needed to further reduce its disease burden in China.